Experimental and numerical analyses of stiffness and fatigue properties of a spring element for mounts with tunable stiffness made of C85S+QT sheet steel (Fracture and Structural Integrity, 2025)
Mounting stiffness has an important impact on a system’s structural dynamics and also on the durability of many structures. Mounts with tunable stiffness allow adapting a system’s structural dynamic behavior. Furthermore, they can be used to emulate elastic behavior of adjacent structures in test benches for components and substructures, e.g. for designing simplified, but accurate fatigue tests. For these applications, the tunable mounts themselves need to have sufficient fatigue strength. In this paper, results of experimental fatigue tests with such mounts are reported, providing material and geometry related fatigue data for four different configurations. Based on these experimental results, numerical parameter studies and analytical correlations, fatigue strength and stiffness approxima-tions are proposed for a wider range of geometries. This enables efficient pre-dimensioning of the tunable mounts starting from basic requirements.
Keywords: Stiffness; fatigue; tunable mounts; S-N curve; component test; FEA